PENGARUH VARIABEL EKONOMI MAKRO TERHADAP PENYALURAN KREDIT UMUM DAN UMKM DI DAERAH ISTIMEWA YOGYAKARTA - Risal Rinofah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2015)
The purpose of this research was to determine the effect of macroeconomic on Generallending and SMEs in Yogyakarta by using multiple linear regression analysis. The variables that will be analyzed are: Inflation, GDP, BI rate and Exchange as the independent variable, while the dependent variable is the General and SME Lending. The results showed no significant simultaneously effect of the macroeconomics variables on general lending and SMEs growth in Yogyakarta. Only Inflation partiallyaffected on lendings growth in Yogyakarta.Â Keywords:Macroeconomics,General Lending and SMEs